Dūra am Tigris im nördlichen Babylonien und der Salzhandel - Kessler, Karlheinz (Anabasis. Studia Classica et Orientalia, 2022)
Only two ancient sources mention the northern Babylonian city of Dūra, located about 12 miles (19 kilometers) south of Tikrit on the eastern bank of the Tigris. According to Polybius, the city was besieged in 221 BC by a general of the mutinous satrap Molon and finally liberated by the army of Antiochus III. In the second source, Ammianus Marcellinus, Dūra appears in 363 AD as a civitas during the Roman retreat under Jovian. This Dūra, however, corresponds to the small modern city of ad-Dūr of the same name. It was the exploitation of salt from a nearby salt lake that made it important in Hellenistic times. This assertion is supported not only by Colonel James Felix Jones’ 1849 travel report, but also by previously unpublished Mandean lead rolls with magical content from the 5th to 7th centuries, which provide us with information about Bīt Dūria and demons, as well as its connection with salt.